2021
DOI: 10.1002/adfm.202007344
|View full text |Cite
|
Sign up to set email alerts
|

Ar/H2/O2‐Controlled Growth Thermodynamics and Kinetics to Create Zero‐, One‐, and Two‐Dimensional Ruthenium Nanocrystals towards Acidic Overall Water Splitting

Abstract: A gas controlled formation strategy is developed to synthesize free‐standing 0D Ru nanoparticles, 1D Ru nanowires, and 2D Ru nanosheets through in‐situ regulated growth thermodynamics and kinetics with typical inert, reductive, and oxidative gases (Ar/H2/O2). The growth process of these Ru nanoparticles, nanowires, and nanosheets follow non‐directional growth, shape‐directed nanoparticle attachment, and directional growth mechanisms, respectively. Kinetics studies approve that H2 accelerates the reduction rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…44 Liang et al accomplished an overpotential of 224 and 236 mV for OER in an acidic medium of HClO 4 with Ru NWs and NSs supported on carbon black. 45 Akbayrak and co-workers have designed a Ru 0 /CeO 2 on a glassy carbon electrode (GCE) for OER, which provides an overpotential of about 380 mV to achieve a current density of 5 mA cm −2 . 46 Likewise, ruthenium nanoclusters@Co 2 P, a Ru–Ni heterostructure/C, RuO 2 /Co 3 O 4 –RuCo@NC, RuO 2 /F doped graphene, Ru with Co doping@CD, Ru/RuS 2 , Ni cluster –Ru nanowires, RuS 2 , and (Ru–Ni)O x require overpotentials of about 197, 357, 247, 239, 257, 201, 194, 282 and 237.2 mV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…44 Liang et al accomplished an overpotential of 224 and 236 mV for OER in an acidic medium of HClO 4 with Ru NWs and NSs supported on carbon black. 45 Akbayrak and co-workers have designed a Ru 0 /CeO 2 on a glassy carbon electrode (GCE) for OER, which provides an overpotential of about 380 mV to achieve a current density of 5 mA cm −2 . 46 Likewise, ruthenium nanoclusters@Co 2 P, a Ru–Ni heterostructure/C, RuO 2 /Co 3 O 4 –RuCo@NC, RuO 2 /F doped graphene, Ru with Co doping@CD, Ru/RuS 2 , Ni cluster –Ru nanowires, RuS 2 , and (Ru–Ni)O x require overpotentials of about 197, 357, 247, 239, 257, 201, 194, 282 and 237.2 mV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from this, there are numerous reports on using ultrathin 2D nanosheets of noble metals for electrocatalysis. [9][10][11][12][13][14][15][16][17][18][19] In addition to the presence of coordinatively unsaturated atoms, a transition from bulk metal to 2D metals can also cause a signicant increase of the active surface area, suggesting an evident advantage over 3D bulk catalysts in terms of a surfacenormalized catalytic activity and a more rational utilization of noble metals. These features highlight the importance of a thorough study of 2DM formation and the need for a deep understanding of fundamental material-property relationships of 2DMs especially in the context of realistic sensing and catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non-noble metal-based materials, noble metal-based electrocatalysts (mainly Pt, Ir and Ru) are irreplaceable as bifunctional electrocatalysts for water electrolysis due to their high intrinsic activity and stability in acidic solution. [13][14][15][16] Among them, Ir/Ru-based and Pt-based electrocatalysts show striking performance in the OER and HER, respectively. [17][18][19][20] Reports have shown that Ru-based catalysts, such as transition-metal-doped RuIr bifunctional nanocrystals, 21 amorphous RuTe 2 porous nanorods, 22 single-site Ptdoped RuO 2 hollow nanospheres with interstitial C, 23 Ru/RuS 2 heterostructures, 24 Ru/RuO 2 heterostructures, 25 and hierarchical IrTe nanotubes 26 have been widely applied to overall water splitting in acidic media.…”
mentioning
confidence: 99%